2009
DOI: 10.3113/fai.2009.0187
|View full text |Cite
|
Sign up to set email alerts
|

Roger Mann Award 2008: Sagittal Plane Motion of the Hindfoot Following Ankle Arthrodesis: A Prospective Analysis

Abstract: This prospective study demonstrated a statistically significant relative hypermobility of the subtalar and medial column joints following ankle arthrodesis, and may account for the functional gait which can be achieved following ankle arthrodesis. The significantly increased subtalar range of movement appeared to cause impingement of the posterior part of the posterior facet of the subtalar joint which may account for the increased incidence of subtalar arthritis following arthrodesis. Preoperative arch height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 35 publications
4
68
2
1
Order By: Relevance
“…Similar to an earlier study, sign of knee hyperextension at terminal stance was also seen in the AAD group in this study [20]. Compensatory motion at the subtalar and midtarsal joints contribute to the amount of ankle dorsiflexion obtained by goniometric measurements and gait analysis [21] and RoM even seems to increase with time after arthrodesis [22]. A compensatory increase of the combined subtalar and medial column motion of 11 % was reported with time after tibiotalar fusion, which also had a positive association of quality of life with increased compensatory motion of the hindfoot and midfoot [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to an earlier study, sign of knee hyperextension at terminal stance was also seen in the AAD group in this study [20]. Compensatory motion at the subtalar and midtarsal joints contribute to the amount of ankle dorsiflexion obtained by goniometric measurements and gait analysis [21] and RoM even seems to increase with time after arthrodesis [22]. A compensatory increase of the combined subtalar and medial column motion of 11 % was reported with time after tibiotalar fusion, which also had a positive association of quality of life with increased compensatory motion of the hindfoot and midfoot [22].…”
Section: Discussionsupporting
confidence: 90%
“…Compensatory motion at the subtalar and midtarsal joints contribute to the amount of ankle dorsiflexion obtained by goniometric measurements and gait analysis [21] and RoM even seems to increase with time after arthrodesis [22]. A compensatory increase of the combined subtalar and medial column motion of 11 % was reported with time after tibiotalar fusion, which also had a positive association of quality of life with increased compensatory motion of the hindfoot and midfoot [22]. In our study, the TAR-alone group showed a significant better outcome of the AOFAS-function subscore compared to the TAR-HFA and AAD groups.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment provides significant pain relief [2,3], but the combined loss of ankle joint mobility can be psychologically challenging [4,5]. Functional evaluation with gait analysis has also revealed that compensatory motion is necessary at the knee and foot joints [6,7]. In addition, alteration of gait parameters [8], stiffness and loss of motion in the subtalar joint [9] have been observed.…”
Section: Introductionmentioning
confidence: 98%
“…Whereas gait analysis has already been employed for the functional assessments of patients following arthroplasty [11,12,14] and arthrodesis [6,8], no such objective instrumental investigation has been performed on BFOA. Therefore the aim of this study was to assess traditional clinical outcomes in ten BFOA patients with modern gait analysis, by providing an objective measure of the function of the main lower limb joints.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that successful unilateral fusion of the ankle in a plantigrade position yields high patient satisfaction and an acceptable functional outcome, there is no question that the sacrifice of the ankle joint will lead to altered hindfoot mechanics. In order to compensate for the loss of ankle mobility, a hypermobility in dorsalextension and plantarflexion of the Chopart joint of up to 21°occurs [74]. Due to the abnormal mechanical loading in the other joints, osteoarthritis as a long-term sequel will occur.…”
Section: Comparison Of Results After Ankle Arthrodesis and Tarmentioning
confidence: 99%